Coping with untranslatability in AVT - Flavia Cavaliere (MediAzioni, 2022)
Many of the most penetrating thinkers over time have focused their attention on the issue of translation and highlighted how translating “may very probably be the most complex type of event yet produced in the evolution of the cosmos” (Richards 1953: 250). In the same vein, Walter Benjamin even maintained that “translations prove to be untranslatable” (Benjamin 1923 in Venuti 2004: 82). Such intricacy may basically be because translation “brings into play not only two languages but also two cultures” (Eco 2001: 62). As a consequence, the extent to which a text is (un)translatable may both depend on the socio-cultural distance between the Source and Target Languages and also on how deeply the text is rooted in its own Source Culture. Additionally, “the cultural implications for translation vary from lexical content and syntax to ideologies and modes of living in a given culture, including genre expectations/constraints” (Cavaliere 2019: 11). This explains why the problems inherent in all translations are at their most evident when translating and adapting a text for the screen. In AVT, in fact, in contrast to other static written modes of communication, the medium prevents both the audience from back-tracking in the text in order to retrieve meaning and, more importantly, the provision of a “thick translation […] that seeks with its annotations and its accompanying glosses to locate the text in a rich cultural and linguistic context” (Appiah 2004: 399). Drawing on the works of well-known translation/AVT scholars, my study will be carried out on English audio scripts of well-known films/TV series and their subtitled/dubbed Italian version (qualitative examples chosen on the basis of their untranslatability will be investigated). My analysis aims to highlight how untranslatability may variously result from differences between linguistic structures to socio-cultural motivations, from the in-built constraints of the medium to the condition of temporality in translation. One of the important functions of translation is to inform about a foreign culture (Levý 2011: 96), and in this perspective, a renewed emphasis on connections among translation, linguistics, philology, philosophy, and socio-cultural issues through easy-to-grasp examples may offer students possibly stimulating (cross)curricular initiatives, especially at advanced undergraduate and graduate levels.